Detecting declines of West African Goliath beetle populations based on interviews - Dendi, D.; Ajong, S.N.; Ségniagbeto, G.H.; Amori, G.; Eniang, E.A.; Fa, J.E.; Demaya, G.S.; Lado, T.F.; Luiselli, L. (Springer, 2023)
Goliath beetles (genus Goliathus) are among the largest and most charismatic insects in the world. In West African forests, two species (G. cacicus and G. regius) and natural hybrids are found. These beetles are widely collected for the entomological trade. We carried out standardized interview campaigns in Liberia and Ivory Coast to explore local persons’ perceptions of the status and population trends of these beetles, as well as information on their ecology and use by humans. Only relatively few interviewed communities reported the presence of beetles, all agreed that Goliath beetle populations were declining, especially G. cacicus. On the other hand, G. regius was generally considered less rare by the interviewees and was also known in a larger number of communities than G. cacicus. Because of the high deforestation rates in Liberia and Ivory Coast, as well as the impact of the international trade at specific collection localities, we suggest that these species are in peril of extinction if no immediate conservation actions are taken to reverse their status.